Association of glycemic control with progression of diabetic retinopathy in type 2 diabetes mellitus patients in Malaysia - Huri, Hasniza Zaman; Chua, Chew Huey; Mustafa, Norasyikin; Mohamad, Nor Fadhilah; Kamalden, Tengku Ain (Universidade de Sao Paulo, 2018)
The risk of having microvascular complication is high among Type 2 Diabetes Mellitus (T2DM) patients. However, factors associated with the glycemic control and progression of diabetic retinopathy (DR) in T2DM patients is limited. This study aims to determine association between anti-diabetic agents, glycemic control and progression of diabetic retinopathy in a Malaysian population. A retrospective study conducted in a tertiary teaching hospital in Malaysia, from January 2009 until March 2014. This study enrolled 104 patients aged 40-84 years, with a mean age 63.12 ± 9.18 years. patients had non-proliferative diabetic retinopathy (NPDR, 77%) and 35% had proliferative diabetic retinopathy (PDR). Diabetic macula edema (DME) was present in 20% of NPDR patients, compared with 7% in PDR. Alpha-glucosidase inhibitor (p=0.012), age (p=0.014) and number of antidiabetic agents used (p=0.015) were significantly associated with stages of diabetic retinopathy. Family history of T2DM (p=0.039) was associated with DME. Identifying factors influencing the progression of diabetic retinopathy may aid in optimizing the therapeutic effects of anti-diabetic agents in T2DM patients.